The Impact of Fintech on Corporate Technology Innovation Based on Driving Effects, Mechanism Identification, and Heterogeneity Analysis - Jianwei Li; Na Li; Xiang Cheng (Discrete Dynamics in Nature and Society)
Fintech relies on emerging technologies such as artificial intelligence and big data to bring a new business model to the financial system; can this new change promote corporate technological innovation? To explore this question, this paper examines the possible impact mechanism of Fintech on enterprise technological innovation based on the examination of the impact of Fintech on enterprise technological innovation through a panel fixed effects model, using A-share listed enterprises in Shanghai and Shenzhen markets in China from 2011–2019, and further explores whether there is heterogeneity in this impact among enterprises with different traits. The results show that Fintech development can significantly promote firm technological innovation and that Fintech can influence firm technological innovation through two mechanisms: alleviating firm financing constraints and providing market opportunities for firms to enhance their profitability. In addition, the driving effect of Fintech on technological innovation is more pronounced in new firms, state-owned enterprises, and nonborrowed and listed firms. Based on the conclusion, it is proposed that the government should enhance certain policy support for Fintech guided by emerging technologies such as artificial intelligence, help Fintech empower the real economy, and at the same time promote the deep integration of Fintech and real enterprises, especially to strengthen the identification of Fintech for new enterprises and encourage state-owned enterprises to implement employee stock ownership system, as well as sound market construction to reduce barriers to listing of high-quality enterprises, so as to improve innovation policy effectiveness and provide a reference for the mitigation of enterprise innovation problems in the new situation.